Geology Structure Identification Using Pre-Stack Depth Migration (PSDM) Method of Tomography Result in North West Java Basin - Sudra Irawan; Muhammad Zainuddin Lubis (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
North West Java Basin is a tertiary sedimentary basin which is located in the right of the western part of the Java island. North West Java Basin is geodynamic where currently located at the rear position of the path of the volcanic arc of Java that is the result of the India-Australia plate subduction to the south towards the Eurasian plate (Explanation of Sunda) in the north. Geology structure observation is difficult to be conducted at Quaternary volcanicfield due to the classical problem at tropical region. In the study interpretation of fault structures can be done on a cross-section of Pre-Stack Depth Migration (PSDM) used prayer namely Hardware Key Device, ie Central Processing Unit: RedHat Enterprise Linux AS 5.0, prayer Monitor 24-inch pieces, Server: SGI altix 450/SuSe Linux Enterprise Server 9.0, 32 GB, 32 X 2,6 GHz Procesor, network: Gigabyte 1 Gb/s, and the software used is paradigm, product: Seismic Processing and Imaging. The third fault obtained in this study in accordance with the geological information derived from previous research conducted by geologists. The second general direction is northwest-southeast direction represented by Baribis fault, fault-fault in the Valley Cimandiri and Gunung Walat. This direction is often known as the directions Meratus (Meratus Trend). Meratus directions interpreted as directions that follow the pattern of continuous arc Cretaceous age to Meratus in Kalimantan.